2017
DOI: 10.2147/ott.s132120
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic roles of IRAK1 in hepatocellular carcinoma tissues: an analysis of immunohistochemistry and RNA-sequencing data from the cancer genome atlas

Abstract: BackgroundIRAK1 has been repoted to play an essential role in the development of multiple cancers. However, the clinical significance of IRAK1 in hepatocellular carcinoma (HCC) and the underlying molecular mechanism remain unclear. Therefore, we aimed to investigate the role of IRAK1 in the pathogenesis of HCC in this study.Materials and methodsHCC tissues and para-carcinoma tissues were collected for immunohistochemistry (IHC) analysis to evaluate IRAK1 expression. Data of IRAK1 expression were downloaded fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…From our data, we observed significant upregulation of IRAK1 and downregulation of IRAK3 and IRAK4 in HCC tissues. This result is consistent to the previous report showing upregulation of IRAK in HCC (16,17). IRAK1 overexpression has also been reported in lung cancer and is associated with clinical TNM stage, lymph node metastasis and tumor size (18).…”
Section: Discussionsupporting
confidence: 93%
“…From our data, we observed significant upregulation of IRAK1 and downregulation of IRAK3 and IRAK4 in HCC tissues. This result is consistent to the previous report showing upregulation of IRAK in HCC (16,17). IRAK1 overexpression has also been reported in lung cancer and is associated with clinical TNM stage, lymph node metastasis and tumor size (18).…”
Section: Discussionsupporting
confidence: 93%
“…IRAK1 is a serine/threonine kinase that plays a key role in the IL1–IL6 axis 41 and has a major role in steatosis associated liver cirrhosis and progression to hepatocellular carcinoma. 42 Knockdown of IRAK1 in human hepatic stellate cells (HSCs) results in reductions in the release of inflammatory cytokines associated with local inflammation and promotion of fibrosis. 43 IRAK1 is critical to signaling by Toll-like receptors activated by fatty acids and other lipid derivatives, and appears to be central to lipid-mediated inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The IRAK family comprises four members, IRAK-1, IRAK-2, IRAK-3 (also known as IRAK-M) and IRAK-4, and has a role in both positive and negative regulation of signal transduction. Recently, it has been shown that IRAK-1 may act as an oncogene in the development of hepatocellular carcinoma [118]. IRAK-4 appears to be indispensable for IL-1R (and TLR) signaling.…”
Section: Targeting the Pi3k Pathwaymentioning
confidence: 99%